Analisis Pengaruh Hari Perdagangan terhadap Return Sahain di Bursa Efek Jakarta - U. Maman Rubaman; Ismail Hamdam (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2005)
Intention of this article idea of initially is to express how far phenomenal anomali market happenedfin Effect Exchange of Jakarta that is going together there is do not it the commeive day influence to daily return share. Pursuant to this tvsearch result obtained byconclusion that realty there is daily difference return share where abnormal of return that happened on Tuesday, Wednesday And Friday statistically own difference which enough signifikan compared to return of share on other commerce.